Degradation Mechanisms of GaN‐Based Vertical Devices: A Review. Issue 7 (22nd January 2020) - Meneghini, Matteo; Fabris, Elena; Ruzzarin, Maria; De Santi, Carlo; Nomoto, Kazuki; Hu, Zhenqi; Li, Wenshen; Gao, Xingya; Jena, Debdeep; Xing, Huili Grace; Sun, Min; Palacios, Tomas; et al.
Abstract : This article reviews most recent results on the reliability of vertical GaN‐based devices, by presenting a few case studies focused on the stability and degradation of high‐voltage GaN‐on‐GaN diodes and of GaN‐based field‐effect transistors (FETs). With regard to diodes, two relevant stress conditions are investigated. The first is operation at high forward current that can induce a degradation of the electrical properties of the devices, mostly consisting in an increase in the operating voltage, well correlated to a decrease in the electroluminescence signal emitted by the diodes. This degradation process is ascribed to the diffusion of hydrogen from the highly p‐type doped regions toward the junction, with consequent compensation of the acceptor (Mg) dopant. The second stress regime investigated on diodes is avalanche: specifically, it is shown that polarization‐doped GaN devices may show avalanche capability, and the stability of diodes in avalanche regime is investigated in detail. With regard to transistors, the analysis is focused on GaN‐on‐GaN vertical Fin‐FETs. First, the stability of the threshold voltage under positive gate stress is analyzed, and the role of interface/oxide traps is discussed by experimental characterization. Then, the degradation under positive gate or high‐drain stress is investigated, to provide information on the dominant degradation processes. Abstract : This article reviews recent results on the reliability of vertical GaN‐based devices, by presenting a number of case studies focused on the stability and degradation of high‐voltage GaN‐on‐GaN diodes and of GaN‐based vertical field‐effect transistors (FETs). These results are of high interest for the optimization of high‐reliability vertical GaN devices.